2014
DOI: 10.4102/jsava.v85i1.992
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the repellent effect of citronella and lemon eucalyptus oil against South African <i>Culicoides</i> species

Abstract: The use of insect repellents to reduce the attack rate of Culicoides species (Diptera:Ceratopogonidae) should form part of an integrated control programme to combat African horse sickness and other diseases transmitted by these blood-feeding midges. In the present study the repellent effects of a commercially available mosquito repellent, a combination of citronella and lemon eucalyptus oils, on Culicoides midges was determined. The number of midges collected with two 220 V Onderstepoort traps fitted with 8 W … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 28 publications
0
12
0
5
Order By: Relevance
“…Recent work has demonstrated that a combination of DEET and plant‐derived organic fatty acids may provide an effective and long‐lasting repellent effect against Culicoides . Citronella oil, while known to be an effective mosquito repellent, has been repeatedly shown to have either no repellent effect or potentially an attractant effect on Culicoides .…”
Section: Prevention Of Culicoides–horse Interactionmentioning
confidence: 99%
“…Recent work has demonstrated that a combination of DEET and plant‐derived organic fatty acids may provide an effective and long‐lasting repellent effect against Culicoides . Citronella oil, while known to be an effective mosquito repellent, has been repeatedly shown to have either no repellent effect or potentially an attractant effect on Culicoides .…”
Section: Prevention Of Culicoides–horse Interactionmentioning
confidence: 99%
“…The use of mesh to protect stabled horses (Barnard, 1997;Meiswinkel et al, 2000) and the efficacy of insect repellents or insecticides applied to mesh surrounding light traps against Culicoides midges have been reported (Braverman and Chizov-Ginzburg, 1998;Page et al, 2009Page et al, , 2014Venter et al, 2011Venter et al, , 2014Del Río et al, 2014a, b). In contrast to the proven efficacy (Lengeler, 2004) and extensive use of pyrethroid-treated mesh against mosquitoes, the use of similar material to protect 3 horses against Culicoides midges has received limited attention (Carpenter et al, 2008a).…”
Section: Introductionmentioning
confidence: 99%
“…The essential oil of C. winterianus showed a protective response that was statistically different from the control after the third accumulated dose (8.75 mg/mL). Cymbopogon winterianus has been cited as a plant with strong repellent properties on mosquitoes and other insects since 1901 [24] . A study by Deletre et al [7] .…”
Section: Resultsmentioning
confidence: 99%